Development of Critical Literacy among Junior High School ‎Students in Language Learning: A Systematic Literature ‎Review - Dewi Quraisyin, Switia; Leiliyanti, Eva; Gomo Attas, Siti (JPI: Jurnal Pustaka Indonesia, 2026)
The development of the digital era requires junior high school students to evaluate information, identify bias, and interpret texts critically, yet language learning often remains focused on basic comprehension. This systematic literature review synthesizes evidence on the concepts, pedagogical strategies, implementation contexts, and assessment approaches used to develop critical literacy among junior high school students in language learning. Studies published from 2020 to 2026 were searched across Scopus, Web of Science, ERIC, ScienceDirect, Taylor & Francis Online, and Google Scholar using predefined Boolean terms. Study selection followed PRISMA 2020 procedures, with independent screening by two reviewers and thematic synthesis of the 12 studies reported in the final review set; methodological quality was appraised using CASP for qualitative studies and JBI tools for quantitative studies. The synthesis indicates that critical literacy is most consistently supported by contextual and active-learning approaches, including problem- or project-based and collaborative learning, critical reading, digital and multimodal texts, and higher-order-thinking-oriented assessment. However, evidence is heterogeneous across language settings, study designs, samples, and assessment tools, limiting direct comparison and transferability. Teacher competence and contextual adaptation emerged as recurrent implementation conditions. The review concludes that critical literacy should be integrated through evidence-based, context-sensitive language pedagogy, while future studies should strengthen methodological consistency, longitudinal evidence, and standardized assessment.